2011
DOI: 10.1007/s10461-010-9875-9
|View full text |Cite
|
Sign up to set email alerts
|

Conversations With Mothers: Exploring Reasons for Prevention of Mother-to-Child Transmission (PMTCT) Failures in the Era of Programmatic Scale-Up in Soweto, South Africa

Abstract: Reasons for incident cases of vertical HIV transmission in the era of free access to PMTCT in South Africa were investigated. This mixed-methods study was conducted in Soweto, South Africa from June-August, 2009. Birthmothers of HIV-infected infants born after 1 December 2008 were eligible. All participants completed an interviewer-administered questionnaire. Women also participated in a focus group (n = 10) or individual structured interview (n = 35). Mean age of participants (n = 45) was 28.7 years (SD = 5.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…Only about 74 % of eligible women were successfully tested for HIV and received their results across conditions, and only 62 % were recruited into the study [37]. Laher and colleagues found that WLH fear the stigma of being identified by others at the clinic as HIV seropositive and, therefore, may not test for HIV nor attend the intervention groups.…”
Section: Limitationsmentioning
confidence: 99%
“…Only about 74 % of eligible women were successfully tested for HIV and received their results across conditions, and only 62 % were recruited into the study [37]. Laher and colleagues found that WLH fear the stigma of being identified by others at the clinic as HIV seropositive and, therefore, may not test for HIV nor attend the intervention groups.…”
Section: Limitationsmentioning
confidence: 99%
“…68 Other contextual factors and challenges contributing to PMTCT failure needs to be taken into account in the planning and delivery of health interventions. The findings of a qualitatively exploration of such factors have highlighted a number of challenges.…”
Section: # #mentioning
confidence: 99%
“…68 Most Strategies to minimise risk of transmission during breastfeeding includes: 66 • EBF during the first 6 months…”
Section: # #mentioning
confidence: 99%
“…Guidelines for PMTCT have been implemented in most HIV-affected countries [4], however, PMTCT program failure and dropout occurs at all stages of the ante-, peri- and postnatal process [5]. Not all pregnant women are tested for HIV [6], not all women receive treatment [7] and not all mothers provided with medication take it themselves or give it to their newborns [8]. Safer infant feeding guidelines are not always followed, not all infants born to HIV-infected mothers are tested and treated [3] and mothers and newborns often miss postpartum clinic visits [9].…”
Section: Introductionmentioning
confidence: 99%